Resilience: Safety in the Aftermath of Traumatic Stressor Experiences - Matheson, Kimberly; Asokumar, Ajani; Anisman, Hymie (Frontiers in Behavioral Neuroscience, 2020)
The relationship between adverse experiences and the emergence of pathology has often focused on characteristics of the stressor or of the individual (stressor appraisals, coping strategies). These features are thought to influence multiple biological processes that favor the development of mental and physical illnesses. Less often has attention focused on the aftermath of traumatic experiences, and the importance of safety and reassurance that is necessary for longer-term well-being. In some cases (e.g., posttraumatic stress) this may be reflected by a failure of fear extinction, whereas in other instances (e.g., historical trauma), the uncertainty about the future might foster continued anxiety. In essence, the question becomes one of how individuals attain feelings of safety when it is fully understood that the world is not necessarily a safe place, uncertainties abound, and feelings of agency are often illusory. We consider how individuals acquire resilience in the aftermath of traumatic and chronic stressors. In this respect, we review characteristics of stressors that may trigger particular biological and behavioral coping responses, as well as factors that undermine their efficacy. To this end, we explore stressor dynamics and social processes that foster resilience in response to specific traumatic, chronic, and uncontrollable stressor contexts (intimate partner abuse; refugee migration; collective historical trauma). We point to resilience factors that may comprise neurobiological changes, such as those related to various stress-provoked hormones, neurotrophins, inflammatory immune, microbial, and epigenetic processes. These behavioral and biological stress responses may influence, and be influenced by, feelings of safety that come about through relationships with others, spiritual and place-based connections.